The influence of using context-based optical instrument e-modules on the scientific literacy of class XI MIPA students at SMAN 12 Padang - Meysi, Nur Afrianti; Desnita, Desnita; Mufit, Fatni; Emiliannur, Emiliannur (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
Since scientific knowledge is the foundation of daily living in the twenty-first century, science literacy is a crucial ability for pupils. But the level of scientific literacy of some students in Indonesia is still low. The test results at SMAN 12 Padang showed that pupils’ level of science literacy wa really low. The fact that instructors’ instructional resources are still not geared toward improving students’ science literacy is one of the reasons why science literacy remains low. One way to increase science literacy is to use context-based physics learning e-modules that are able to connect science concepts with real everyday topics or problems. This research seeks to determine the effects of utilizing optical instrument e-modules on the science literacy of class XI students of SMAN 12 Padang. This study used a control group in a quasi-experimental setup that is only tested after the test. The participants in this study were SMAN 12 Padang class XI Mipa students. The sampling process used the purposive sampling technique. The sample in this study was 35 students of class XI Mipa 3 and 36 students of class XI Mipa 4. The study’s findings come from the science literacy abilities of the students. Aspects of students' science literacy skills include science competencies, knowledge, context, and attitudes. Data collection was carried out by descriptive tests of 11 questions and questionnaires. The instruments utilized in this investigation were written tests in the form of questionnaires and descriptive inquiries. The hypothesis test’s findings yielded a computed tvalue = 4.007 and a t table value = 1.995 at a significance level of α = 0.05. Because the hypothesis is accepted at a significance level of 0.05. Considering the outcomes, it can be said thet using e-module optical instruments has a beneficial influence on the scientific knowledge of class XI Mipa students of SMAN 12 Padang.